Engineering biophysical interactions through micro- to nanocavity emissions - Yuan, Zhiyi (Nanyang Technological University, 2023)
Optical micro and nanoresonators have attracted tremendous attention owing to their fruitful physical phenomenon and extraordinary capability to confine light in ultrasmall mode volume. To date, a plethora of biological applications based on cavity emissions have been demonstrated by taking advantage of enhanced light-matter interactions. Advantages of employing cavity-enhanced detection include significantly improved detection sensitivity and signal-to-noise ratio. Despite the great progress, most studies emphasized on the quantitative parameters of biomolecules (analyte concentrations or detection limit), which does not reflect the qualitative property of the target. Less attention has been paid toward the intrinsic biophysical features of molecules, hindering its application for multidimensional sensing. Therefore, this dissertation aims to investigate and explore biophysical light-matter interactions through micro and nanoscale cavity emissions. For better understanding of biological detection through cavity emissions, we begin with a brief review of the basic mechanisms of optical micro-resonators and emissions (Chapters 1 and 2). In the first two projects (Chapters 3 and 4), we focus on the development of sensing mechanism of microscale biological lasers. A novel concept was thus developed to achieve lasing-encoded microsensors by utilizing light-harvesting effect at the cavity interface. Distinct lasing spectra could therefore distinguish molecules of different absorption properties upon binding. Taking advantage of this phenomenon, both protein-based and enzymatic-based sensing reactions were demonstrated and quantified through laser emission wavelengths. Next in Chapters 5 and 6, we investigated the possibility of extracting molecular polarizations and chirality through biological microlaser emissions. The concept of molecular lasing polarization was proposed, in which small molecules such as peptides and metabolites could be distinguished by lasing polarization. Additionally, the concept and mechanism of chiral light-matter 15 interactions under stimulated emission process was carried out by exploiting active resonators. Chirality transfer under stimulated emission process was also studied between fluorescent proteins and organic dye molecules. Our results show that circular dichroism signal could be enhanced by two-three orders of magnitude through stimulated emission process in a microcavity. Finally, the concept of biological plasmonic exciton systems was proposed, offering the possibility of using such system to characterize biomolecular interactions and activities from microscale to nanoscale. While previous chapters focused on spectral information of bio-cavity emission, Chapter 7 demonstrates an efficient far-field imaging tool for direct characterizing multiple nanocavity emissions from weak to strong coupling regimes. The key findings in this study may provide new prospects in laser physics and light-matter interactions for biophysical sensing and imaging.